BANF1 is a novel prognostic biomarker linked to immune infiltration in head and neck squamous cell carcinoma - He, Yaodong; Li, Huan; Li, Jing; Huang, Junhong; Liu, Rong; Yao, Yanbing; Hu, Yating; Yang, Xinjie; Wei, Jianhua (Frontiers in Immunology, 2024)
Background: Barrier-to-autointegration factor 1 (BANF1) is an abundant and ubiquitously expressed postnatal mammalian protein that is overexpressed in numerous human cancers and can promote cancer cell proliferation. However, the role of BANF1 in prognosis remains unclear in head and neck squamous cell carcinoma (HNSCC).Methods: BANF1 expression data were obtained from the GEO and TCGA databases. We used Cox regression and Kaplan -Meier curves to assess the prognostic potential of BANF1. The role of BANF1-related genes was investigated using Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) enrichment analyses. In addition, we explored the link between BANF1, drug sensitivity, and the tumor immune microenvironment. Finally, functional in vitro and in vivo assays were used to explore the effects of BANF1 on tumor growth and metastasis of HNSCC.Results: BANF1 was markedly overexpressed in HNSCC and was correlated with clinicopathological characteristics. According to survival analysis, BANF1 can be inversely correlated with patient survival and can act as a prognostic risk indicator. IC50 values for chemotherapeutic treatments indicated that the group with high BANF1 expression was more responsive to most antitumor treatments. Furthermore, higher TIDE scores were observed in the low BANF1 expression group, indicating a decline in the efficacy of immune checkpoint inhibitor therapy. Functionally, the malignant biological behavior of HNSCC cell lines was inhibited when BANF1 expression was knocked down.